THE PROCESS APPROACH IN WRITING SKILL AND ITS TEACHING - Abdullayeva Shahnoza Akbaraliyevna (Research Focus International Scientific Journal, 2023)
The article deals with the nature of the writing skill. First, it makes a distinction between writing and speaking in terms of nature and teaching, and then it looks in detail at the exact nature of the writing skill investigating the causes of its difficulty. The second problem is concerned with teaching writing according to the process approach highlighting its various features and problems. Another aspect that is dealt with in this article is peer review which is an important component of the process approach.